The impact of plasmablade on cardiac implantable electronic device generator replacement procedures - Olgun, Fatih Erkam; Yıldırım, Ersin; Demir, Gültekin Günhan; Kılıçaslan, Fethi (AVES, 2022)
[Abstract Not Available]
Keywords: Electronic Device Generator; PlasmaBlade; Cardiac Implantable